Robert Williams - the father of exponential imagination drawings, paintings, & sculptures - Reynolds, Eric 1971- (Fantagraphics Books, 2019)
"This career retrospective showcases the 'lowbrow' artist's 'realistic' oil paintings, drawings, sculptures, and works in other media. This is a comprehensive, career-spanning, collection of the iconic painter's fine art, including every one of his oil paintings, along with a selection of his drawings, sculptures, and multimedia works. Williams pursued a career as a fine arts painter years before joining the art studio of Ed 'Big Daddy' Roth in the mid-1960s. From this position, he moved into the rebellious, anti-war circles of early underground comix, as one of the celebrated Zap cartoonists. Featuring an introductory essay by Coagula Art Journal founder Mat Gleason, along with a new art manifesto and foreword by Williams himself (the former of whom brought the term 'lowbrow' into the fine arts lexicon), as well as tons of rare photos and ephemera. Full-color Illustrations throughout."--Publisher's description
Umschlagtitel
Keywords: Williams, Robert -- 1943-; Williams, Robert / 1943- / Catalogs; Grotesque in art / Catalogs; Painting, American / 20th century; Williams, Robert / 1943-; Painting, American; Grotesque in art; 1900-1999; Catalogs; Bildband; Werkverzeichnis